Railway superstructure for high-speed rails - Lukáš Týfa; Jan Kruntorád; Ondřej Tomaschko (Acta Polytechnica CTU Proceedings)
The construction of the track is solved as a conventional (with track ballast) or as a ballastless track (without track ballast). When deciding on the choice of the most suitable track design for high-speed rail, it is necessary to emphasize that with increasing line speed, the requirements for the quality of the track geometry increase, including the size of the deviations of individual geometric parameters of the track from the projected values. When assessing the choice of track structure – especially for high-speed rails – it is therefore necessary and correct to assess the total costs (investment and operational) for a sufficiently long time. DB Netz AG’s present experience with a ballastless track since its first implementation in 1972 in Rheda station, for almost 50 years, shows that the required lifetime of 60 years has its real justification. In addition, current research and development in the field of ballastless track is moving towards extending the life of ballastless track well beyond this limit. The paper is focused on the comparison a ballasted and ballastless track construction. It deals in more detail with evaluation of the advantages and disadvantages of a ballastless track construction. The main objective is to assess the use of ballastless track structure for the construction of high-speed lines.